NILAI KETAKTERATURAN TOTAL SISI DARI GRAF TANGGA (STAIR GRAPH) - Wulandari, Septiyani Setyo; Slamin, S; Setiawani, Susi (KadikmA, 2014)
Abstract. The total edges labelling Î» is called an edge irregular total k-labelling of a graph G if every two distinct edges u and v in G Ït(u)â Ït(v). The total edge irregularity strength of G is the minimum positive integer k for which G has a total edge irregular k-labelling. There are not many graphs of which their total edge irregularity strengths are known. In this article, we investigate the total edge irregularity strength of Stair Graph tes(Stn) and union of m isomorphic Stair Graphs tes(mStn). Key Words: Total edge irregularity strength, Stair Graph (Stn).